2020
DOI: 10.7150/ijms.42151
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Immune Infiltration in Bladder Cancer and its Clinical Significance: an Integrative Genomic Analysis

Abstract: Tumor-infiltrating immune cells are closely related to the prognosis of bladder cancer. Analysis of tumor infiltrating immune cells is usually based on immunohistochemical analysis. Since many immune cell marker proteins are not specific for different immune cells, which may induce misleading or incomplete. CIBERSORT is an algorithm to estimate specific cell types in a mixed cell population using gene expression data. In this study, the CIBERSORT algorithm was used to identify the immune cell infiltration sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…is result was consistent with previous results, which suggested that tumor-infiltrating neutrophils were associated with a high risk of disease recurrence and poor overall survival outcomes [31]. A previous study revealed better overall survival rates in bladder cancer patients with high regulatory T-cell infiltration levels [32]. In our study, we found a negative correlation between regulatory T-cell infiltration levels and the risk score.…”
Section: Discussionsupporting
confidence: 93%
“…is result was consistent with previous results, which suggested that tumor-infiltrating neutrophils were associated with a high risk of disease recurrence and poor overall survival outcomes [31]. A previous study revealed better overall survival rates in bladder cancer patients with high regulatory T-cell infiltration levels [32]. In our study, we found a negative correlation between regulatory T-cell infiltration levels and the risk score.…”
Section: Discussionsupporting
confidence: 93%
“…Innate and adaptive immune response are involved during bladder cancer. Prognosis and sensitivity to treatment of bladder cancer are related to tumor-infiltrating immune cells, and understanding the immune response could be the starting point for the development of personalized therapy and precision medical treatments [71].…”
Section: Resultsmentioning
confidence: 99%
“…In the era of numerous genetic prognostic factors in bladder cancer [25][26][27][28], there is an urgent need for easily accessible, affordable, and widely interpretable biomarkers for current practice. The Neutrophil-to-lymphocyte Ratio proves to have all these benefits [29][30][31].…”
Section: Discussionmentioning
confidence: 99%